Lipid-based microparticles for targeted release systems for aquaculture - Yap, Jia Yi (Nanyang Technological University, 2021)
Nutrient delivery in aquaculture is affected by the leaching losses of the nutrients in the water environment, which makes it inefficient in delivering the required doses to the fish’s body. Protection via microencapsulation can be a viable method for preventing leaching losses as well as delivering nutrients to specific parts of the fish’s GI tract. This study was undertaken to fabricate methionine, an essential amino acid, encapsulated solid lipid microparticles (SLMs) by melt emulsification and spray chilling. Melt emulsification is a simple method which disperses the nutrient into a melted lipid and emulsified to a heated polar phase. Microparticles produced by melt emulsification in this study have a size ranging from 100-500μm. However, it is not a scalable technique for commerialisation. Whereas spray chilling is a scalable method by atomising melted lipid with nutrients into a cold chamber. Spray chilling has the advantage of high production efficiency and produce smaller microparticles ranging from 12-48μm. Leaching protection capabilities of the SLMs produced by these methods were also evaluated in simulated environments of aquaculture i.e. aqueous, gastric and intestinal. SLMs demonstrated excellent leaching protection in aqueous environment while ensuring release in the simulated intestinal environment. In addition, a hybrid alginate-lipid bead was also fabricated with floating and sinking abilities to deliver the SLMs according to the feeding behaviors of different fishes. To optimise the fabrication process, freeze drying and vacuum oven drying were investigated. Vacuum oven was found to be the suitable method for drying the alginate-lipid beads. These results support the use of lipid walled microparticles as a targeted delivery vehicle in aquaculture setting for delivery of amino acids as well as other nutrients.